Connecting learning to the world beyond the classroom through collaborative philosophical inquiry. Issue 5 (19th October 2016) - Scholl, Rosie; Nichols, Kim; Burgh, Gilbert
ABSTRACT: This study explored the impact of facilitating collaborative philosophical inquiry (CPI), in the tradition of "Philosophy for Children, " on connectedness pedagogies. The study employed an experimental design that included 59 primary teachers in 2 groups. The experimental group received an intervention that comprised training in CPI and the comparison group received training in Thinking Tools (graphic organisers), a subset of the CPI training. Lessons were coded on four variables of connectedness pedagogies, across the two groups, at three time-points. Teacher interviews were conducted to gather participants' perspectives. Between-groups analysis of variance (ANOVA) on particular measures of pedagogy revealed that CPI significantly broadened teachers' pedagogical repertoires, in ways that included drawing on students' background knowledge and preparing a problem-based curriculum which connects students to the world beyond the classroom.